Preparation method and application of polyimide-fluoromica composite coating slurry

Through the preparation method of polyimide-fluoromica composite coating slurry, the insufficient performance problems of circuit board packaging materials in miniaturization, lightweighting and high reliability are solved, and high thermal conductivity, pressure resistance, high temperature resistance and Low cost effect, suitable for integrated circuit packaging.

CN119144225APending Publication Date: 2024-12-17ZHEJIANG ROUHE NEW ENERGY MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411429754.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing circuit board packaging materials have insufficient performance in terms of miniaturization, lightweighting and high reliability, especially the problems of high internal stress of epoxy resin, high production cost and poor adhesion of silicone materials, which are difficult to meet the needs of electronic products. High thermal conductivity, pressure resistance, high temperature resistance and cost control requirements.

Method used

The preparation method of polyimide-fluoromica composite coating slurry is adopted, and the preparation of synthesis of PI precursor solution, nanofluoromica and ball milling are uniformly dispersed with the catalyst. The high-level heating reaction is prepared by using segmented heating. A composite coating slurry that is thermally conductive, pressure-resistant and high temperature-resistant.

Benefits of technology

It has achieved the improvement of high thermal conductivity, pressure resistance, high temperature resistance, lightweight, sealing and fatigue performance of polyimide-fluoromica composite coating slurry. It is suitable for integrated circuit packaging, with low cost and good stability. Suitable for miniaturized and lightweight circuit board design.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of polyimide-fluoromica composite coating slurry, which comprises the following steps: synthesizing a PI precursor solution: drying 4, 4-diaminodiphenyl ether and pyromellitic dianhydride, dissolving the dried 4, 4-diaminodiphenyl ether in a DMF (Dimethyl Formamide) solvent, adding the pyromellitic dianhydride in batches, and stirring to obtain a PAA (Polyacrylamide) solution; the preparation method comprises the following steps: synthesizing nano fluoromica, adding nano fluoromica particles and a catalyst into a PAA solution, continuously stirring in an environment of 30-80 DEG C, and carrying out ball milling to obtain a PAA / fluoromica mixed solution; and putting the PAA / fluoromica mixed solution into a muffle furnace for amidation, and carrying out segmented heating to obtain the polyimide-fluoromica composite coating slurry. The polyimide-fluoromica composite coating slurry has the advantages that the preparation is simple, the preparation cost is low, and the prepared polyimide-fluoromica composite coating slurry has high thermal conductivity, good pressure resistance, high temperature resistance, light weight, good sealing performance and good fatigue performance, and is suitable for packaging of integrated circuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of integrated circuit packaging, in particular to a preparation method and application of a polyimide-fluoromica composite coating slurry. Background Art

[0002] With the rapid development of integrated circuit chips and material technology, packaging technology has also ushered in a breakthrough improvement, and the requirements for packaging material performance are becoming increasingly stringent. Electronic packaging not only requires materials to have excellent electrical, thermal and mechanical properties, but also emphasizes high reliability and cost control, which is also the main reason why packaging resins can occupy the mainstream material position of modern electronic packaging. Traditional circuit boards achieve waterproof and anti-corrosion functions by applying three-proof glue on their surfaces. However, with the rapid development of electronic technology, electronic products are gradually moving towards miniaturization, lightweight, high-speed, multi-functionality and high reliability. To adapt to this trend, the design of circuit boards is also developing in the direction of miniaturization, lightweight and high density.

[0003] Epoxy resin has become the most widely used packaging material due to its excellent adhesion, dielectric properties, sealing, electrical insulation and transparency. However, the cured epoxy resin will cause greater internal stress due to its high crosslinking density, which will affect its impact resistance, present a greater brittleness, and sometimes lead to separation from the internal packaging interface. In addition, the main chain of the silicone material is Si-O-Si, the side group is methyl, and the entire molecular chain is helical. This special heterochain molecular structure gives it many excellent properties, such as high light transmittance, good thermal stability, strong UV resistance, low internal stress, low hygroscopicity, etc. Patent application CN108165014A provides a packaging method with strong adhesion, good toughness and high reliability, and adds a series of materials such as silicone, mica and carbon fiber to prepare packaging glue. However, the production cost of silicone materials is relatively high, and when silicone materials are used as potting and coating materials, their adhesion is relatively poor, which will affect the normal operation of electronic products.

[0004] Polyimide (PI) materials have excellent high temperature stability, electrical insulation performance, excellent chemical stability, and good mechanical properties. This series of properties is of great significance for improving the stability and reliability of electronic equipment. Fluoromica is a layered structure material composed of silicate minerals. It has good thermal conductivity, and the thermal conductivity of fluoromica will gradually increase with the increase of temperature. In addition, fluoromica has excellent electrical insulation performance, high temperature resistance, corrosion resistance, high transparency, good stability and good elasticity. It is not only an ideal material for manufacturing high-performance electronic components, but also very suitable for use in the manufacture of electronic, electrical and metallurgical equipment in high temperature environments.

[0005] Therefore, it is urgent to propose a circuit packaging adhesive with high thermal conductivity, good pressure resistance, low cost, high temperature resistance, light weight, good sealing and good fatigue performance to meet the development of overall miniaturization and lightweight of circuit boards. Summary of the invention

[0006] The purpose of the present invention is to disclose to the public a preparation method of a polyimide-fluoromica composite coating slurry and its application. The preparation method is simple and the preparation cost is low. The prepared polyimide-fluoromica composite coating slurry has high thermal conductivity, good pressure resistance, low cost, high temperature resistance, light weight, good sealing and fatigue performance, and is suitable for integrated circuit packaging.

[0007] The technical solution of the present invention is achieved in this way: A method for preparing a polyimide-fluoromica composite coating slurry comprises the following steps: Step 1, synthesizing PI precursor solution: 4,4-diaminodiphenyl ether and pyromellitic anhydride are placed in an oven for drying at a mass ratio of 1:1-1.2, 4,4-diaminodiphenyl ether after drying is dissolved in DMF solvent, and mechanically stirred at 0-10°C; pyromellitic anhydride is added in batches and stirred to obtain a yellow, clear and transparent PAA solution; Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension, then adding sodium fluoride and potassium chloride to continue stirring and reacting for 1-24 hours, during which time sodium hydroxide solution is added to the suspension to adjust the pH value of the solution to neutral; centrifuging to obtain a precipitate, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping the temperature for 1-2 hours, calcining and gradually cooling to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica, and crushing the fluorine mica into nano-fluorine mica particles; Step 3: Add nano-fluoromica particles and a catalyst to the PAA solution, continue stirring in an environment of 30° C. to 80° C., and then use a ball mill to perform ball milling to obtain a PAA / fluoromica mixed solution; Step 4: Place the PAA / fluoromica mixed solution in a muffle furnace for amidation, control the heating rate to 3°C / min-10°C / min, and adopt segmented heating to obtain a polyimide-fluoromica composite coating slurry.

[0008] In the step 1, the oven temperature is controlled at 80°C-180°C, and the drying time is controlled at 1.5h to 2.5h.

[0009] In the step 1, the process of adding pyromellitic anhydride in batches for stirring is: adding one-half of the total mass of pyromellitic anhydride to the mixed solution and stirring, then adding the remaining one-half of the mass of pyromellitic anhydride to the mixed solution and continuing to stir, and finally adding the remaining pyromellitic anhydride to the mixed solution to continue the reaction.

[0010] In the step 3, the total mass ratio of the PAA liquid to the fluoromica and the catalyst is 10:1.

[0011] In the step 3, the mass ratio of PAA liquid to fluoromica is 1:0.01-0.05.

[0012] In the step 3, the catalyst is dibutyltin dilaurate or SICAT-03.

[0013] In the step 3, the stirring speed is controlled at 200 rpm-1500 rpm, and the stirring time is controlled at 0.5 h-2 h.

[0014] In the step 3, the ball milling time is controlled within a range of 10 min to 120 min.

[0015] In the step 4, the segmented heating is specifically: heating at 50°C-180°C for 2h, heating at 200°C for 0.5h, heating at 220°C-290°C for 0.5h, and heating at 300°C-350°C for 0.5h.

[0016] An application of a polyimide-fluoromica composite coating slurry is applied to integrated circuit packaging.

[0017] The advantages of the present invention are: The preparation method of the polyimide-fluoromica composite coating slurry of the present invention is simple to prepare and has low preparation cost. The prepared polyimide-fluoromica composite coating slurry has high thermal conductivity, good pressure resistance, high temperature resistance, light weight, good sealing and fatigue performance, and is suitable for packaging of integrated circuits. In order to solve the problem of easy aggregation of nano-fluoromica particles, a chemical synthesis method is introduced by a catalyst to uniformly disperse the fluoromica particles in a mixed solution to prepare a polyimide-fluoromica composite coating slurry with good dispersibility, which does not precipitate or deteriorate, and improves the slurry stability.

[0018] After testing, the polyimide-fluoromica composite coating slurry prepared by the present invention is coated on an integrated circuit, and the encapsulation layer formed can withstand a high temperature of 1300°C, a compressive strength of 2kV, a tensile strength of 150-600MPA, an impact strength of 200-400KJ / ㎡, a thermal conductivity of 0.15-0.25W / (m·K), and a coating density of only 1-10g / cm 3 . DETAILED DESCRIPTION

[0019] A method for preparing a polyimide-fluoromica composite coating slurry comprises the following steps: Step 1: Synthesize PI precursor solution: Place 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) in an oven at 80℃-180℃ in a mass ratio of 1:1-1.2 and dry for 1.5h to 2.5h. Dissolve the dried 4,4-diaminodiphenyl ether in DMF solvent and stir mechanically at 0-10℃ for 10min-60min. Add pyromellitic anhydride in batches and stir to obtain a yellow, clear and transparent PAA solution. The process of adding pyromellitic anhydride in batches is: add one-half of the total mass of pyromellitic anhydride to the mixed solution and stir for 10min-60min, then add one-half of the remaining mass of pyromellitic anhydride to the mixed solution and continue stirring for 10min-60min, and finally add the remaining pyromellitic anhydride to the mixed solution and continue reacting for 40min-240min. Adding pyromellitic anhydride in batches can control viscosity and prevent violent polymerization.

[0020] Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension (liquid-solid ratio of 1-5:1), then adding sodium fluoride and potassium chloride (1:1) and continuing to stir and react for 1-24 hours, during which sodium hydroxide solution is continuously added to the suspension to adjust the pH value of the solution to neutral; obtaining a precipitate by high-speed centrifugation at 500-1200 rad / min, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping the temperature for 1-2 hours, calcining and gradually cooling to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica; placing the fluorine mica in a high-speed mechanical ball mill, and crushing it into nano-fluorine mica particles by high-speed physical impact (speed of 30-120 rad / min, ball milling time of 1-24 hours).

[0021] Step 3: Add nano-fluorine mica particles and catalyst to the PAA solution, continue stirring for 0.5h-2h in an environment of 30℃-80℃, control the stirring speed at 200rpm-1500rpm, and then use a ball mill for ball milling, and control the ball milling time at 10min-120min to obtain a PAA / fluorine mica mixed solution. Among them, the total mass ratio of PAA solution to fluorine mica and catalyst is 10:1, and the mass ratio of PAA solution to fluorine mica is 1:0.01-0.05; the above-mentioned catalyst is dibutyltin dilaurate or SICAT-03. Here, the PI precursor solution is modified by fluorine mica and catalyst.

[0022] Step 4: Place the PAA / fluoromica mixture in a muffle furnace for amidation, control the heating rate to 3°C / min-10°C / min, and adopt segmented heating to obtain a polyimide-fluoromica composite coating slurry. The heating rate is preferably 5°C / min. The segmented heating is specifically: heating at 50°C-180°C for 2h, heating at 200°C for 0.5h, heating at 220°C-290°C for 0.5h, and heating at 300°C-350°C for 0.5h.

[0023] The present invention synthesizes a PI precursor solution, adds fluoromica and a catalyst for modification, and then obtains a composite coating slurry through an in-situ reaction by high-temperature heat treatment. The prepared composite slurry combines the excellent insulation, heat resistance and mechanical strength of the PI material with the high thermal conductivity and chemical stability of the fluoromica material, and is suitable for use in integrated circuit packaging.

[0024] The following is further described by specific embodiments: Example

[0025] Step 1: Synthesize PI precursor solution: 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were placed in an oven at 100°C for drying for 2 hours in a mass ratio of 1:1 to remove moisture; the dried ODA was dissolved in 50 ml of DMF solvent and mechanically stirred for 30 minutes at 2°C; one-half of the mass of PMDA was added to the mixed solution and stirred for 30 minutes, and then the remaining one-half of the mass of PMDA was added to the mixed solution and continued to stir for 30 minutes, and finally the remaining PMDA was added to the mixed solution and continued to react for 200 minutes to obtain a yellow, clear and transparent PAA solution.

[0026] Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension (liquid-solid ratio of 2:1), then adding sodium fluoride and potassium chloride (1:1) and continuing to stir and react for 1-24 hours, during which sodium hydroxide solution is continuously added to the suspension to adjust the pH value of the solution to neutral; obtaining a precipitate by high-speed centrifugation at 500-1200 rad / min, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping it warm for 1-2 hours, calcining and gradually cooling it to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica; placing the fluorine mica in a high-speed mechanical ball mill and crushing it into nano-fluorine mica particles by high-speed physical impact (speed of 60 rad / min, ball milling time of 18 hours).

[0027] Step 3: Add nano-fluoromica particles and catalyst (dibutyltin dilaurate) to the PAA solution in a mass ratio of 10:1 and a mass ratio of PAA to fluoromica of 1:0.02. Continue stirring at 40°C for 2 hours at a stirring speed of 500 rpm, then use a ball mill for 50 minutes to obtain a PAA / fluoromica mixed solution.

[0028] Step 4: Place the PAA / fluoromica mixture in a muffle furnace for amidation, heat at 100°C for 2h, 200°C for 0.5h, 250°C for 0.5h, and 300°C for 0.5h, with a heating rate of 5°C / min, to obtain a polyimide-fluoromica composite coating slurry. Example

[0029] Step 1: Synthesize PI precursor solution: 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were placed in an oven at 100°C for drying for 2.2 hours in a mass ratio of 1:1.2 to remove moisture; the dried ODA was dissolved in 80 ml of DMF solvent and mechanically stirred for 50 minutes at 4°C; one-half of the mass of PMDA was added to the mixed solution and stirred for 40 minutes, and then the remaining one-half of the mass of PMDA was added to the mixed solution and stirred for 40 minutes, and finally the remaining PMDA was added to the mixed solution and continued to react for 180 minutes to obtain a yellow, clear and transparent PAA solution; Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension (liquid-solid ratio of 3:1), then adding sodium fluoride and potassium chloride (1:1) and continuing to stir and react for 1-24 hours, during which sodium hydroxide solution is continuously added to the suspension to adjust the pH value of the solution to neutral; obtaining a precipitate by high-speed centrifugation at 500-1200 rad / min, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping it warm for 1-2 hours, calcining and gradually cooling it to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica; placing the fluorine mica in a high-speed mechanical ball mill and crushing it into nano-fluorine mica particles by high-speed physical impact (speed of 120 rad / min, ball milling time of 12 hours).

[0030] Step 3: Add nano-fluorine mica particles and catalyst (SICAT-03) to the PAA solution in a mass ratio of 10:1, and a mass ratio of PAA to fluorine mica of 1:0.04. Continue stirring for 2 h at 40°C with a stirring speed of 1000 rpm, and then use a ball mill for ball milling for 70 min to obtain a PAA / fluorine mica mixed solution. Step 4: Place the PAA / fluoromica mixture in a muffle furnace for amidation, heat at 120°C for 2h, 200°C for 0.5h, 260°C for 0.5h, and 330°C for 0.5h, with a heating rate of 6°C / min, to obtain a polyimide-fluoromica composite coating slurry. Example

[0031] Step 1: Synthesize PI precursor solution: 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were placed in an oven at 100°C in a mass ratio of 1:1.1 and dried for 1.5 hours to remove moisture; the dried ODA was dissolved in 100 ml of DMF solvent and mechanically stirred for 30 minutes at 10°C; one-half of the mass of PMDA was added to the mixed solution and stirred for 50 minutes, and then the remaining one-half of the mass of PMDA was added to the mixed solution and continued to stir for 50 minutes, and finally the remaining PMDA was added to the mixed solution and continued to react for 120 minutes to obtain a yellow, clear and transparent PAA solution.

[0032] Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension (liquid-solid ratio of 4:1), then adding sodium fluoride and potassium chloride (1:1) and continuing to stir and react for 1-24 hours, during which sodium hydroxide solution is continuously added to the suspension to adjust the pH value of the solution to neutral; obtaining a precipitate by high-speed centrifugation at 500-1200 rad / min, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping it warm for 1-2 hours, calcining and gradually cooling it to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica; placing the fluorine mica in a high-speed mechanical ball mill, and crushing it into nano-fluorine mica particles by high-speed physical impact (speed of 30 rad / min, ball milling time of 24 hours).

[0033] Step 3: Add fluoromica and catalyst (dibutyltin dilaurate) to the PAA solution in a mass ratio of 10:1 and a mass ratio of PAA to fluoromica of 1:0.05. Continue stirring at 60°C for 1 hour at a stirring speed of 1500 rpm, then use a ball mill for 100 minutes to obtain a PAA / fluoromica mixed solution.

[0034] Step 4: Place the PAA / fluoromica mixture in a muffle furnace for amidation, heat at 60°C for 2h, 200°C for 0.5h, 220°C for 0.5h, and 310°C for 0.5h, with a heating rate of 4°C / min, to obtain a polyimide-fluoromica composite coating slurry.

[0035] Comparative Example Step 1: Synthesize PI precursor solution: 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were placed in an oven at 100°C for drying for 2 hours in a mass ratio of 1:1 to remove moisture; the dried ODA was dissolved in 50 ml of DMF solvent and mechanically stirred for 30 minutes at 2°C; one-half of the mass of PMDA was added to the mixed solution and stirred for 30 minutes, and then the remaining one-half of the mass of PMDA was added to the mixed solution and stirred for 30 minutes, and finally the remaining PMDA was added to the mixed solution and continued to react for 200 minutes to obtain a yellow, clear and transparent PAA solution; Step 2: Place the PAA solution in a muffle furnace for amidation, heat at 100°C for 2h, 200°C for 0.5h, 250°C for 0.5h, and 300°C for 0.5h, with a heating rate of 5°C / min, to obtain a polyimide coating slurry.

[0036] The slurries prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to thermal conductivity tests, and the results showed that the thermal conductivity of the slurry in Example 1 was 0.21 W / (m·K), the thermal conductivity of the slurry in Example 2 was 0.23 W / (m·K), the thermal conductivity of the slurry in Example 3 was 0.22 W / (m·K), and the thermal conductivity of the comparative example was 0.18 W / (m·K). This indicates that the thermal conductivity of the slurry can be greatly improved by modifying the fluorine mica.

[0037] After testing, the polyimide-fluoromica composite coating slurry prepared by the present invention is coated on an integrated circuit, and the encapsulation layer formed can withstand a high temperature of 1300°C, a compressive strength of 2kv, a tensile strength of 150-600MPA, and an impact strength of 200-400KJ / m 2 The thermal conductivity is 0.15-0.25W / (m·K), and the coating density is only 1-10g / cm 3 .

[0038] The best embodiment of the present invention has been described, and various changes or modifications may be made by those skilled in the art without departing from the scope of the present invention.

Claims

1. A method for preparing a polyimide-fluoromica composite coating slurry, characterized in that: The following steps are involved: Step 1, synthesizing PI precursor solution: 4,4-diaminodiphenyl ether and pyromellitic anhydride are placed in an oven for drying at a mass ratio of 1:1-1.2, 4,4-diaminodiphenyl ether after drying is dissolved in DMF solvent, and mechanically stirred at 0-10°C; pyromellitic anhydride is added in batches and stirred to obtain a yellow, clear and transparent PAA solution; Step 2, synthesizing nano-fluorine mica: adding nitric acid solution to nano-mica particles to react to obtain a liquid-solid suspension, then adding sodium fluoride and potassium chloride to continue stirring and reacting for 1-24 hours, during which time sodium hydroxide solution is added to the suspension to adjust the pH value of the solution to neutral; centrifuging to obtain a precipitate, heating the precipitate to 1000°C at a heating rate of 5°C / min-10°C / min, keeping the temperature for 1-2 hours, calcining and gradually cooling to obtain a crude fluorpho-mica product; using supercritical carbon dioxide to peel off the crude fluorpho-mica product to obtain fluorine mica, and crushing the fluorine mica into nano-fluorine mica particles; Step 3, adding nano-fluoromica particles and a catalyst to the PAA solution, continuing to stir in an environment of 30° C.-80° C., and then using a ball mill to perform ball milling to obtain a PAA / fluoromica mixed solution; Step 4: Place the PAA / fluoromica mixed solution in a muffle furnace for amidation, control the heating rate to 3°C / min-10°C / min, and adopt segmented heating to obtain a polyimide-fluoromica composite coating slurry.

2. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 1, the oven temperature is controlled at 80°C-180°C, and the drying time is controlled at 1.5h to 2.5h.

3. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 1, the process of adding pyromellitic anhydride in batches for stirring is: adding one-half of the total mass of pyromellitic anhydride to the mixed solution and stirring, then adding the remaining one-half of the mass of pyromellitic anhydride to the mixed solution and continuing to stir, and finally adding the remaining pyromellitic anhydride to the mixed solution to continue the reaction.

4. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 3, the total mass ratio of PAA liquid to fluoromica and catalyst is 10:

1.

5. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 3, the mass ratio of PAA liquid to fluoromica is 1:0.01-0.

05.

6. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 3, the catalyst is dibutyltin dilaurate or SICAT-03.

7. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 3, the stirring speed is controlled at 200 rpm-1500 rpm, and the stirring time is controlled at 0.5 h-2 h.

8. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 3, the ball milling time is controlled within a range of 10 min to 120 min.

9. The method for preparing a polyimide-fluoromica composite coating slurry according to claim 1, characterized in that: In the step 4, the segmented heating is specifically: heating at 50°C-180°C for 2h, heating at 200°C for 0.5h, heating at 220°C-290°C for 0.5h, and heating at 300°C-350°C for 0.5h.

10. An application of a polyimide-fluoromica composite coating slurry, characterized in that: Applied to integrated circuit packaging.

Citation Information

Patent Citations

  • Preparation method of friction-reducing and wear-resisting polymer-based composite

    CN105924965A

  • Sodium bismuth titanate-barium titanate / polyimide-based dielectric composite material and preparation method thereof

    CN109626992A

  • Preparation method of fluorphlogopite mica, and application of fluorphlogopite mica in preparation of two-dimensional crystals

    CN109694078A

  • An alumina nanoparticle / polyimide based energy-storage medium and a preparing method thereof

    CN109776828A

  • Polyimide composite material with double-layer structure with extreme environmental tolerance and preparation method thereof

    CN111499911A